2019
DOI: 10.1108/jstpm-12-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Mobile commerce adoption among the bottom of the pyramid: a case of street vendors in Thailand

Abstract: Purpose This study aims to investigate the applicability of technology acceptance model in explaining technology adoption among street vendors in Thailand as a representation of emerging economies. Design/methodology/approach A pen-and-pencil survey was administered to 370 street vendors in Bangkok; 356 usable surveys were analyzed for a completed rate of 96.2 per cent. Structural equation modeling was used to analyze the data. Findings This study contributes to the existing technology acceptance literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 66 publications
3
29
0
1
Order By: Relevance
“…The second-best predictor of intent to use m-commerce was perceived trust. This confirmed that trust is a critical component of economic transactions in online environments ( Ashraf et al., 2014 ; Flavián and Guinalíu, 2006 ; Gefen et al., 2003 ; Gefen and Straub, 2004 ; Hansen et al., 2018 ; Nguyen and Huynh, 2018 ; Nor and Pearson, 2007 ; Pavlou, 2003 ; Sing and Matsui, 2017 ; Tan and Sutherland, 2004 ), and is positively related to the adoption of e-payment, m-payment and m-banking by consumers in Vietnam, Thailand, the Republic of Korea and the United Kingdom ( Nguyen and Huynh, 2018 ; Pipitwanichakarn and Wongtada, 2018 ; Shaikh and Karjaluoto, 2015 ; Shin, 2009 ; Slade et al., 2013 ). In fact, the first online purchase study of the Electronic Commerce Observatory of Ecuador suggested that more than 70% of Ecuadorians interviewed named trust as the main reasons for not making online purchases, and 44.9% declared that they did not buy in national portals for reasons related to lack security and support during the purchase process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second-best predictor of intent to use m-commerce was perceived trust. This confirmed that trust is a critical component of economic transactions in online environments ( Ashraf et al., 2014 ; Flavián and Guinalíu, 2006 ; Gefen et al., 2003 ; Gefen and Straub, 2004 ; Hansen et al., 2018 ; Nguyen and Huynh, 2018 ; Nor and Pearson, 2007 ; Pavlou, 2003 ; Sing and Matsui, 2017 ; Tan and Sutherland, 2004 ), and is positively related to the adoption of e-payment, m-payment and m-banking by consumers in Vietnam, Thailand, the Republic of Korea and the United Kingdom ( Nguyen and Huynh, 2018 ; Pipitwanichakarn and Wongtada, 2018 ; Shaikh and Karjaluoto, 2015 ; Shin, 2009 ; Slade et al., 2013 ). In fact, the first online purchase study of the Electronic Commerce Observatory of Ecuador suggested that more than 70% of Ecuadorians interviewed named trust as the main reasons for not making online purchases, and 44.9% declared that they did not buy in national portals for reasons related to lack security and support during the purchase process.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of emerging markets do not have to parallel the assumptions made by theories derived from developed markets, industrialized countries (Burgess and Steenkamp, 2006), or in countries in which technology adoption is the maturity stage already (Pipitwanichakarn and Wongtada, 2018). It is necessary to strengthen the technology adoption theoretical body that will explain what drives the use of technology in the BOP segment and develop accurate and reliable ICT acceptance behavioral models (Zaremohzzabieh et al, 2016) in order to guide organizations in the development of successful, profitable and sustainable initiatives supported by technology.…”
Section: Emerging Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study confirms that perceived usefulness, perceived ease of use, IT trust, level of e-commerce adoption, security, and IT infrastructure significantly impact the adoption of m-commerce. Pipitwanichakarn and Wongtada (2019) extend TAM for investigating organizational m-commerce adoption in Thailand. The study indicates that perceived usefulness, perceived ease of use, trust, and entrepreneurial orientation are the critical determinants for the adoption of m-commerce.…”
Section: Organizationsmentioning
confidence: 99%
“…At a glance, the growth of mobile businesses appears promising (Pipitwanichakarn and Wongtada, 2019;Park et.al., 2019;Choe, 2018;eMarketer, 2017). Along with the development of mobile internet services, more and more consumers are adopting smartphones as their main communication device.…”
Section: Introductionmentioning
confidence: 99%